Entre a tradição e a disciplina: o que há de filósofo no professor de filosofia? - Souza, Carlos Miguel da Silva (2021)
Our question appears from an intimate agitation, from the anguish that frightens those who dedicate themselves profoundly to a task. This agitation, when it appears, does not relate to any specific aspect of the task. In our case, the philosophy teacher’s job, what worries is not what content must be applied over what methods and teaching techniques. It is not the didactic that leaves us unsettled, neither the definition of the philosophy’s curriculum to be applied in schools. It is also not up to us to ask teachers a modus operandi in the classroom. All these things are exceedingly necessary to the teaching gesture. And all these worries, amongst other things that arise in the daily routine and the classroom, to the teacher concerns. What moves us, whether we notice or not, is that each student who crosses the classroom door asks the following question: what it means to be a teacher? Thus, we comprehend this question as a radical one, since it leads us to the foundations of who we are. In this bibliographic theoretical research, where the main question makes it present in the title, we investigate the relation between the teacher’s work, the study of the philosophic tradition, and its disciplinary development in the classroom. These aspects do not oppose themselves, on the contrary, they belong to each other. To achieve this main goal, we disposed at first a state of the art, where we studied the contemporary Brazilian productions about the teacher-philosopher, followed by a dissertated chapter divided into four sections, where we discuss sequentially: a) The language’s fundamental question; b) The deconstruction of the subject through writing; c) The teaching of philosophy as recipience, hospitality; d) The philosophy teachers’ work as ethical-political engagement. As a theoretical foundation, we critically discussed Jacques Derrida (2017), Martin Heidegger (2012), Peter Sloterdijk (2018), Lopes e Macedo (2011), Jorge Larrosa (2018) e Brayner de Farias (2018). If reason, the rationale being does not deplete the possibilities of being in the world, the interpretative manner that presents itself as a rigorous interpretation of the human being which its habitat is in language. Our most intimate evaluations and discourses on which we adhere without even notice are ties, traces, interpretative tessituras that build us while this or that in which we recognize as our name. And as to how these lines never stop intertwine, weave, cut, tore apart, and lock it, we can create other threads. The closure can be overcome by comprehending that the human being itself is language. We, teachers of philosophy, have the ethical responsibility to reinterpret things. Meaning is poiesis